The nexus between media transparency and attitude for risk management during a disaster / Juliana Mohd Abdul Kadir ... [et al.] - Mohd Abdul Kadir, Juliana; Zakaria, Nor Balkish; Abd Aziz, Noreen Noor; Premananto, Gancar Candra (Accounting Research Institute (ARI), 2022)
The government has taken drastic measures to control the spread of virus transmission during the Covid-19 disaster. In a Movement Control Order, the public was advised to stay at home and practice social imprisonment of infected persons for risk management purposes. The government has spread public awareness and encouraged the public to stay safe and healthy from infectious viruses using media channels. The mass media plays a significant role in providing information and understanding about the disease and helps protect the elderly and those with basic health problems from being infected. This research examined: (1) the role of media transparency on public awareness and knowledge of the infected virus, which in turn influences their attitudes; (2) to determine the influence of media transparency on the attitudes of the people. A survey method was applied to 338 respondents consisting of young people living in Johor. Data were analysed using SmartPLS, and the findings indicated that the role of media transparency has a significant impact on the attitudes of this generation Z. In addition, it was also found that awareness and knowledge mediated the role of media and their attitudes. These findings can guide policymakers to promote greater awareness to reduce and manage possible risks during disasters. Moreover, the media plays an important role not only in channeling news but can influence human awareness, knowledge, and attitudes.